Health risks of fake foods and benefits of modern ergogenic dietary supplements for sports - Lysenko, A. V.; Stepanova, T. A.; Vassel, S. S.; Lysenko, D. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to summarize the many years` experience in the in-house studies on the development of optimal algorithms for using modern ergogenic aids to improve the results in elite sports, as well as enhance the healthcare effect of trainings in amateur sports (based on the nutrients approved by WADA). Methods and structure of the study. During the experiment, we analyzed the effects of more than 20 biologically active peptides on the body of athletes and representatives of population groups, the vital activity of which is associated with the influence of various adverse environmental and professional factors. We described the authors` express test developed on the basis of a refractometric analysis and designed to detect food adulteration, and proved its higher efficiency in comparison with the organoleptic method. Results of the study. The perspectives of using peptide-based biologically active food additives is confirmed by a major impact of in-house experimental studies and literature data indicating the ability of short peptides (mainly consisting of 3-4 amino acids) to interact with DNA, thus regulating gene expression, which results in a large number of positive effects on the human body. An important aspect of the mechanism of action of short peptides is their effect on the intensity of lipid peroxidation. Conclusion. The analysis of the experimental data on the mechanisms of action and effects of the studied peptides and their complexes (such as pinealon, cortexin, noopept, and many others) suggests the possibility of using biologically active food additives based on short peptides as a safe alternative to pharmacological drugs in order to increase physical working capacity and mental performance, stress tolerance, learning ability, sports records while maintaining health and achieving active longevity.